Do Pro-Poor Schools Reach Out to the Poor? Location Choice of BRAC and ROSC Schools in Bangladesh - Asadullah, M.N. (Wiley, 2016)
Location choice of ‘one teacher, one classroom’ non-formal primary schools pioneered by Bangladesh Rural Advancement Committee (BRAC) is studied vis-à-vis its replication under government-managed Reaching-Out-of-School (ROSC) project using school Census data. Both types of schools have a statistically significant presence in poor sub-districts within a district. However, BRAC schools avoid pockets that lack public infrastructure and suffer from female illiteracy, while ROSC schools have greater presence in regions that have poor access to cities and roads. Moreover, ROSC schools better target regions that are under-served by government schools; the opposite is true for BRAC schools and state-recognised madrasas.